Differential Radiomodulating Action of Olea europaea L. cv. Caiazzana Leaf Extract on Human Normal and Cancer Cells: A Joint Chemical and Radiobiological Approach - Severina Pacifico; Pavel Bláha; Shadab Faramarzi; Francesca Fede; Katarina Michaličková; Simona Piccolella; Valerio Ricciardi; Lorenzo Manti (MDPI AG, 2022)
The identification of a natural compound with selectively differential radiomodulating activity would arguably represent a valuable asset in the striving quest for widening the therapeutic window in cancer radiotherapy (RT). To this end, we fully characterized the chemical profile of olive tree leaf polyphenols from the Caiazzana cultivar (OLC), autochthonous to the Campania region (Italy), by ultra-high-performance liquid chromatography-high-resolution mass spectrometry (UHPLC-HR-MS). Oleacein was the most abundant molecule in the OLC. Two normal and two cancer cells lines were X-ray-irradiated following 24-h treatment with the same concentration of the obtained crude extract and were assessed for their radioresponse in terms of micronucleus (MN) induction and, for one of the normal cell lines, of premature senescence (PS). Irradiation of pre-treated normal cells in the presence of the OLC reduced the frequency of radiation-induced MN and the onset of PS. Conversely, the genotoxic action of ionising radiation was exacerbated in cancer cells under the same experimental conditions. To our knowledge, this is the first report on the dual action of a polyphenol-rich olive leaf extract on radiation-induced damage. If further confirmed, these findings may be pre-clinically relevant and point to a substance that may potentially counteract cancer radioresistance while reducing RT-associated normal tissue toxicity.